Analisis Literatur: Efektivitas Model Pembelajaran Terpadu Tipe Webbed dalam Memberikan peningkatan Hasil Belajar Siswa Sekolah Dasar - Apit Pamungkas; Usri Maharyati; Menik Handayani; Siti Nurjanah; Rodiyatun; Ajib Hermawan (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze the effectiveness of the webbed-type integrated learning model in improving elementary school students’ learning outcomes through a literature analysis approach. The method employed is a literature study using document search techniques through Google Scholar with the assistance of Publish or Perish software. From 579 identified articles, a selection process based on publication years (2021–2025) and topic relevance resulted in 18 eligible articles. The findings indicate that the webbed integrated learning model consistently demonstrates effectiveness in improving students’ learning outcomes, including cognitive achievement, skills, and literacy. This effectiveness is influenced by systematic thematic integration, increased student engagement and learning activities, as well as the use of instructional media and innovations. Furthermore, the model contributes to the enhancement of literacy interest, writing skills, and scientific literacy. However, variations in implementation and research design affect the generalizability of the findings. Therefore, further studies employing quantitative meta-analysis are recommended to strengthen the validity of results